FENOMENA PHUBBING DI ERA MILENIA (Ketergantungan Seseorang pada Smartphone terhadap Lingkungannya) - Hanika, Ita Musfirowati (Interaksi: Jurnal Ilmu Komunikasi, 2015)
AbstractAs a new word, phubbing is a term that created by the combination of phone and snubbing. It refers to someone that interacting with their phone (or other device) rather than communicate with interlocutors. This reality happened on modern society who lives in urban areas. The aims of this study to find out the provoke someone who could be a phubber that imply to interpersonal communication. The research was using polling desing with 50 sampels who could represent the population. This research was conducted at Communication Postgraduate Diponegoro University. Eventhough the majority of respondents did not know about phubbing, they ever did it with any reasons. The background of its reality is happened due to media dependency and the excessive anxiety not to use the device. Another finding revealed that respondents who did phubbing is getting annoyed if the other person did the same things.